Coinminer malware detection using Python script / Nur Nabilah Muhammad Azlan Jefre - Muhammad Azlan Jefre, Nur Nabilah (2020)
The project is about development of CoinMiner Malware Detection using Python. The reason for developing this project is to give enlightenment towards computer users on how to detect coinminer malware. Nowadays coinminer malware has been actively spread among corporate networks. It took over a computer's resources and used them for mining cryptocurrency illegally without a user's permission. Consistently, systems like Bitcoin, Dash, and Litecoin become evermore unified. Moreover, there are also an increasing number of reported cases where malicious coinmining code has been infecting user’s machines for the purpose of illegal mining. Mining has become more of a problem than a solution. Furthermore, users are also unaware that their computer resources have been used for mining which lead to financial loss. This project is needed to give an awareness towards corporate networks about coinminer malware. It is also to suggest Coinminer Malware Detection using Python Script as a new detection method for coinminer malware in a corporate network. The goal of this project is to help the users of corporate networks to detect the coinminer malware and avoid them from being a victim. The limitation and suggestion for future enhancement of this project had been identified based on the analysis of the data collected.